Boat maintenance for both powerboats and sailboats (Safe boating series ;, 2004)
Maintenance tips for thru-hulls & sea cocks, plumbing, batteries & electrical, marine head rebuild, reciprocal bearings, diaphram water pump, impeller water pump, varhishing, bolting to the deck, and much, much more.